Bioconversion of Microalga Chlorella sp. as an Alternative Energy for Biofuel in Fishery Waste Media - Endah Rochmatika; Ahmad Shofy Mubarak; Win Darmanto (Jurnal Ilmu Pertanian Indonesia, 2025)
Carbon dioxide emissions from burning fuel oil have been increasing, resulting in increasingly severe climate change. The use of microalgae as raw materials for biofuel production is an environmentally friendly alternative. Microalgae Chlorella sp. can be sustainably converted into alternative biofuels. Fishery liquid waste, such as that resulting from fish farming and fish processing, can be used as a nutrient medium for microalgae. This study aimed to analyze biomass production from Chlorella sp. using fishery waste in an algae reactor. The working principle of fisheries wastewater processing is related to microalgae in the reactor. The surface of the media forms a biological layer that breaks down organic compounds in the air, thereby reducing the organic content. The compounds resulting from metabolic processes are in the form of solids and gases. The results show that the bioethanol produced from the thermostat Chlorella sp. with fishery waste media can produce 20,000 L/ha. Microalgae contain approximately 20-50% dry weight of carbohydrates, which can be converted into bioethanol. Chlorella sp. can reduce chemical oxygen demand and ammonia by up to 70% by converting carbon dioxide into carbohydrates, fats, and proteins. The application of bioconversion to all companies in the fisheries sector will provide benefits and help the government reduce fossil fuel subsidies. Keywords: bioconversion, biofuel, fisheries, microalgae, waste